Merging wine and tourism-related services: evidence from the Douro (Portugal) Wine Region. (2nd October 2019) - Guedes, Alexandre; Rebelo, João
ABSTRACT: This article examines the supply structure and merging level of tourism-related services of wineries, focusing on a set of internal and external resources, namely corporate information, wine, tourism-related services/activities, information about the wine region inter-institutional network. A sample of 25 wine companies which own 103 wineries in the Douro Wine Region (DWR) are examined and enhanced with seven international wine regions as a benchmark. Results suggest that wineries exhibit an adaptive and atomized organization which is based on mutualistic cooperation between wine and tourism rather than being founded on a core product-supplementary services norm. The benchmarking analysis indicates that the parameters that define the online positioning of wineries in the DWR are in line with the best practices worldwide.